THE EFFECT OF ADDING TEMPE FLOUR AND TIME OF PROLONG BOILING ON THE QUALITY OF THE OYSTER MUSHROOM SAUSAG ( PLEUROTUS OSTREATUS) - Masyhura MD ,; Mhd. Iqbal Nusa; Wahyu Andriyeni (AGRIUM: Jurnal Ilmu Pertanian, 2016)
The research on the effect of adding tempe flour and time of prolong boiling on the quality of the oyster mushroom sausage ( pleurotus ostreatus) with Design Random Complete Method with two (2) replications. Factor I is the concentration of tempe flour that is: K1=5%, K2=10%, K3=15%, K4=20%. Factor II is long boiling (L) consisting of four levels, that is: L1 = 15 minute, L2 = 20 minute, L3 = 25 minute, dan L4 = 30 minute. The parameters observed: protein, water content, texture, organoleptic aroma and flavor. The statistical analysis was obtained, that Consentration tempe flour providing highly significant effect (P<0.01) to protein, water content, texture, organoleptic aroma  and flavor. The long boiling  providing highly significant effect (P<0.01)     to water content, texture,organoleptic aroma, and flavor and had no significant effect (P>0.05)   to protein.Keyword: Sausage, Oyster Mushroom, Tempe Flour, Time of Prolong Boiling